Support Students to Learn – Use of TetraMap® to Shift our Mindset in Emergency Remote Teaching - Ivy CHAN; Carmen SUM; Joyce CHENG (Communications of International Proceedings, 2020)
The outbreak of COVID-19 has swept its abrupt impacts in education around the globe.  The higher education institutions in Hong Kong are in no exception.  Instructors of a business subject were given limited time to plan, design, and implement emergent remote teaching, which is a transformation from conventional face-to-face teaching.  To meet the ends, the instructors adopted the TetraMap® model, and deployed the four nature elements to shift the mindset on pedagogical design of various learning and teaching materials for 344 students.  Without enormous adoption towards high-end technologies, the instructors made the mindset shift to explore new solutions that support students in their learning amid the coronavirus pandemic.  The results were encouraging that positive feedback on emergent remote teaching was well received from students. Educators may further explore the application of TetraMap® model in their online and face-to-face teaching.
Keywords: mindset; emergent remote teaching; learning